Uso do simulador Tinkercad: relato de experiência em uma escola de ensino profissionalizante - (:unkn) unknown (Universidade Federal do Pampa, 2025)
Considering the technological advancements in society, especially digital ones, the use of direct tools and components for conducting electronic experiments and simulations has been reduced, particularly due to the advancement of software that allows for virtual simulations with safety and reliability equivalent to experimentation with physical electronic equipment. In this sense, this work aims to present an experience report on an activity using the TinkerCad simulation environment to build basic circuit designs linked to the subjects of Analog Electronics, C Programming Language, and Technical Drawing, associated with the professional technical course in Electrotechnics at a school in the Guaiba-RS municipality, so that once the basic circuits were executable, their construction could be carried out using equivalent electronic equipment. The activity was carried out in two phases. The first consisted of building simulations of electro-electronic circuits in the TinkerCad environment, and the second was the construction of the projects using electro-electronic resources on a breadboard. Considering the observations in the post-activity questionnaire, it is noted that activities such as the one presented here contribute significantly to improving the quality of teaching, especially in vocational courses. Finally, the importance of more research activities involving the use of simulation environments/softwares in the classroom setting is highlighted, from different perspectives and using different software and/or resources.
Keywords: Educação Profissionalizante; Eletrônica; Simuladores; Professional Education; Electronics; Simulators; MULTIDISCIPLINAR